2020
DOI: 10.1021/acschembio.0c00308
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon-Stitched Peptide Agonists of Glucagon-Like Peptide-1 Receptor

Abstract: Glucagon-like peptide 1 (GLP-1) is a natural peptide agonist of the GLP-1 receptor (GLP-1R) found on pancreatic β-cells. Engagement of the receptor stimulates insulin release in a glucosedependent fashion and increases β-cell mass, two ideal features for pharmacologic management of type 2 diabetes. Thus, intensive efforts have focused on developing GLP-1-based peptide agonists of GLP-1R for therapeutic application. A primary challenge has been the naturally short half-life of GLP-1 due to its rapid proteolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
(119 reference statements)
1
14
0
Order By: Relevance
“…Taken together, HDX provides a high precision read-out of stapling effects on the peptide structure and proteolytic resistance, as recently demonstrated for hydrocarbon-stitched GLP1 peptides. 34 Our SAH-gp41 (638−673) (E) results highlight that when proteolytic resistance is derived more from the sequence-specific staple protection rather than α-helical induction, HDX naturally favors the detection of the conformational rather than the proteolytic changes. Thus, coupling the MS analyses with the study resistance patterns to multiple proteases should prove useful in distinguishing between the effect of hydrocarbon stapling on peptide conformation and the localized protection of vulnerable sequences.…”
Section: ■ Materials and Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Taken together, HDX provides a high precision read-out of stapling effects on the peptide structure and proteolytic resistance, as recently demonstrated for hydrocarbon-stitched GLP1 peptides. 34 Our SAH-gp41 (638−673) (E) results highlight that when proteolytic resistance is derived more from the sequence-specific staple protection rather than α-helical induction, HDX naturally favors the detection of the conformational rather than the proteolytic changes. Thus, coupling the MS analyses with the study resistance patterns to multiple proteases should prove useful in distinguishing between the effect of hydrocarbon stapling on peptide conformation and the localized protection of vulnerable sequences.…”
Section: ■ Materials and Methodsmentioning
confidence: 87%
“…In vitro proteolysis testing was the most sensitive method for detecting the differential impact of staple variants on the structural stability and, most profoundly, the stability profile was predictive of in vivo activity. 34 However, to our knowledge IM-MS has yet to be leveraged in stapled peptide assessments. Enfuvirtide (Enf) is a 36-residue fusion inhibitor peptide that was approved by the FDA in 2003 for the treatment of HIV-1.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eluant was directed into a Waters Synapt G2si mass spectrometer operated in TOF-only mode for mass analysis. Data were analyzed as described 22 , 40 . All mass spectra were processed manually using MagTran.…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely used for the diagnosis and treatment of T2DM. Recent studies have suggested that GLP-1 can inhibit bone resorption by promoting the secretion of calcitonin[ 3 ]. Matrix Gla protein (MGP) is a circulating protein related to vitamin K that can inhibit calcium and phosphorus deposition and play a role in the regulation of bone metabolism[ 4 ].…”
Section: Introductionmentioning
confidence: 99%